NOTCH1 Signalling: A key pathway for the development of high-risk chronic lymphocytic leukaemia - Edelmann, Jennifer (Frontiers in Oncology, 2022)
NOTCH1 is a cell surface receptor that releases its intracellular domain as transcription factor upon activation. With the advent of next-generation sequencing, the NOTCH1 gene was found recurrently mutated in chronic lymphocytic leukaemia (CLL). Here, virtually all NOTCH1 mutations affect the protein’s PEST-domain and impair inactivation and degradation of the released transcription factor, thus increasing NOTCH1 signalling strength. Besides sequence alterations directly affecting the NOTCH1 gene, multiple other genomic and non genomic alterations have by now been identified in CLL cells that could promote an abnormally strong NOTCH1 signalling strength. This renders NOTCH1 one of the key signalling pathways in CLL pathophysiology. A rising frequency of NOTCH1 related alterations over the disease course and their association with transformation of CLL into an aggressive lymphoma (Richter transformation) implies a causal link between abnormally strong NOTCH1 signalling and the development of a high risk disease character. This narrative review provides data on the role of NOTCH1 mutation for CLL development and progression, discusses the impact of NOTCH1 mutation on treatment response, gives insight into potential modes of NOTCH1 pathway activation and regulation, summarises alterations that have been discussed to contribute to a de regulation of NOTCH1 signalling in CLL cells and provides a perspective on how to assess NOTCH1 signalling in CLL samples.